AB0212 A study to determine the relationship between fatigue, physical activity and sitting time in patients with inflammatory arthritis. (23rd January 2014) - Fitzpatrick, D.; Mcgowan, B.; McPartland, A.; Silke, C.; Whelan, B.
Abstract : Background: Fatigue is a common and debilitating symptom in inflammatory arthritis. Higher levels of physical activity are associated with better general health status and with better outcomes in inflammatory arthritis [1 ]. Objectives: Our aim was to measure fatigue and physical activity in those with inflammatory arthritis and to examine the relationship between the two. Methods: The study involved the use of two validated self-administered questionnaires 1) the FACIT-F questionnaire[2 ], to measure fatigue and wellbeing and 2)(the long version of the International Physical Activity Questionnaire (IPAQ)[3 ] in consecutive, unselected patients with a diagnosis of inflammatory arthritis (rheumatoid arthritis, psoriatic arthritis and juvenile idiopathic arthritis) attending the NWRU. The nonparametric results were analysed with Spearman correlation and Mann-Whitney U techniques. Results: 63 patients were recruited. The mean age of the study cohort was 59.4 years with mean disease duration of 12 years. There was a positive correlation between sitting-time and fatigue score (R =.482, p<.05) and a negative correlation between sitting-time and physical wellbeing score (R=.406, p<.05). There is a weaker negative correlation between fatigue score and physical activity (R=.252, p<.05). Conclusions: As expected, fatigue is related negatively with physical activity. However, the positive relationship between fatigue and sitting-time is stronger and more significant. The utility of asking patients how much time they spend sitting to gauge physical activity and fatigue merits further investigation. References: J. Cooney, R. Law, and V. Matschke, "Benefits of exercise in rheumatoid arthritis, " Journal of aging, 2011. "FACIT-F." [Online]. Available: http://www.facit.org/FACITOrg/Questionnaires . [Accessed: 28-Jun-2012]. "International Physical Activity Questionnaire (Long Form)." [Online]. Available: http://www.ipaq.ki.se/ . [Accessed: 28-Jun-2012]. Disclosure of Interest: None Declared